Translation, Cross-cultural Adaptation and Psychometric Properties of the Parental Feeding Style Questionnaire into Brazilian Portuguese Language - de Sousa, Karina Guedes (2023)
Objective: To translate, cross-culturally adapt and test the psychometric properties of the Parental Feeding Style Questionnaire (PFSQ) to Brazilian Portuguese language. Material and Methods: Three stages were carried out: 1st, the 27-item of PFSQ was translated, back-translated, reviewed by a Committee of Experts and pre-tested (n=60), obtaining the cross-culturally adapted version. 2nd, the final version was self-applied by 42 mothers for internal consistency (Cronbach’s Alpha). After 2-weeks, 19 mothers answered the PFSQ again for reproducibility (Intraclass Correlation Coefficient, ICC). 3rd, 204 mothers of children aged 4-5 years answered the PFSQ for translation validation [convergent validity and exploratory factor analysis (EFA)]. Results: For subscales, Cronbach’s alpha ranged from 0.65 to 0.82; the overall reliability was 0.69, indicating substantial internal consistency. The ICC for overall PFSQ was 0.78 and for domains 0.56-0.89, indicating moderate to excellent reproducibility. ‘Control over eating’ correlated positively with ‘prompting/encouragement to eat’ and negatively with ‘instrumental feeding’; ‘prompting/encouragement to eat’ correlated positively with ‘emotional feeding’. By EFA, PFSQ items were loaded on four factors. ‘Control over eating’ and ‘prompting/encouragement to eat’ settled into two factors, whereas the ‘emotional’ and ‘instrumental feeding’ domains into one factor each. Conclusion: Despite the different factors found by AFE related to the original PFSQ, the reliability was satisfactory, making the Brazilian Portuguese version of the PFSQ adequate to assess parental feeding style.